Bimbingan Dan Pelatihan Kader Muda Imam Serta Khatib Kecamatan Garung Dan Mojotengah Kabupaten Wonosobo - Samsul Munir; Soffan Rizqi; Fatkhurrohman Fatkhurrohman; Mukromin Mukromin; Asyhar Kholil; Robingun Suyud El Syam (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Da'wah activities are activities carried out by preachers by calling for goodness and preventing evil things in order to achieve happiness in this world and the hereafter. Among the management carried out by the Muslim community is how to develop prospective cadres of imams and preachers for Friday prayers. The aim of this service is to find out how to guide and train young cadres of imams and preachers, Garung & Mojotengah District, Wonosobo Regency. This community service was carried out on October 8 2023, in Mojotengah sub-district. The service is carried out in several stages, the first stage is the explanation of the theory to the participants. The second stage is the training stage carried out by the resource person. The research results concluded that this guidance and training activity produced young cadres of imams and preachers who understand and can carry out their profession as imams and preachers properly and correctly. After being given theoretical knowledge through lecture and discussion methods, the training participants were given space to practice being imams and preachers in these activities. In this way, guidance and training participants have abilities not only theoretically but also practically. This activity is expected to produce a community that understands and can carry out Friday sermons.